Crataegus azarolus Leaves Induce Antiproliferative Activity, Cell Cycle Arrest, and Apoptosis in Human HT‐29 and HCT‐116 Colorectal Cancer Cells. Issue 5 (5th November 2015) - Mustapha, Nadia; Pinon, Aline; Limami, Youness; Simon, Alain; Ghedira, Kamel; Hennebelle, Thierry; Chekir‐Ghedira, Leila
ABSTRACT: Limited success has been achieved in extending the survival of patients with metastatic colorectal cancer (CRC). There is a strong need for novel agents in the treatment and prevention of CRC. Therefore, in the present study we evaluated the antiproliferative and pro‐apoptotic potential of Crataegus azarolus ethyl acetate extract in HCT‐116 and HT‐29 human colorectal cancer cell lines. Moreover, we attempted to investigate the signaling pathways that should be involved in its cytotoxic effect. The Crataegus azarolus ethyl acetate extract‐induced growth inhibitory effect was associated with DNA fragmentation, sub‐G1 peak, loss of mitochondrial potential, and poly (ADP‐ribose) polymerase (PARP) cleavage. In addition, ethyl acetate extract of Crataegus azarolus induced the cleavage of caspase‐8. It has no effect on steady‐state levels of total Bcl‐2 protein. Whereas Bax levels decreased significantly in a dose‐dependent manner in both tested cell lines. Taken together, these findings confirm the involvement of the extrinsic pathway of apoptosis. The apoptotic cell death induced by ethyl acetate extract of Crataegus azarolus was accompanied by an enhancement of the p21 expression but not through p53 activation in human colorectal cancer cells. The above‐mentioned data provide insight into the molecular mechanisms of Crataegus azarolus ethyl acetate extract‐induced apoptosis in CRC. Therefore, this compound should be a potential anticancer agent for the treatment of CRC. J. Cell. Biochem. 117: 1262–1272, 2016. © 2015 Wiley Periodicals, Inc.